THE ROLE OF SPIRITUAL REFORMS IN PERFECT HUMAN UPBRINGING - Raximov G‘ayrat Buvaxanovich (Journals Park Publishing, 2023)
Over the years, great achievements have also been made in the spiritual and educational spheres of our country. Since the first years of our independence, the creation of changes in society in Uzbekistan, the bringing of our country to the ranks of developed countries, the promotion of democratic principles, the promotion of the spiritual life of society, and the transformation of members of society into spiritually perfect persons have formed the basis of the policies that our state is pursuing.
Keywords: promotion of democratic principles, the promotion of the spiritual life of society, and the transformation of members of society